The counteractive illustration and its metalanguage. Issue 4 (2nd October 2018) - Petersson, Sonya
Abstract: Illustration may be thought of as a picture relating to the text in a containing medium, such as a book. Here, however, the objective is to reconsider some of the conceptual conventions surrounding the pictorial genre, by way of using illustrations as productive of their own metalanguage or of a language that refers to illustration as a media phenomenon. Illustrations taken from the Swedish nineteenth-century magazine Ny Illustrerad Tidning are inserted into a framework of historiographic texts on the genre of illustration, by nineteenth-century writers such as Henry Blackburn and P. G. Hamerton, and present concepts about media and media interrelations, most notably W. J. T. Mitchell's 'imagetext'. Rather than test the illustrations' capability of accommodating the juxtaposed texts and concepts, the study makes a case for their ability to counteract—negotiate, complicate, adjust, sidestep, or discard—the terms initially on offer. From a close analysis of the illustrations' media properties, in relation to the conceptual material, the study solicits from the illustrations a metalanguage that defers the conventional separation of image and text, and displaces the idea of an original preceding the medium of reproduction. In conclusion, the study argues for two aspects that give cause to reconsider some conventional assumptions about the genre of illustration and move beyond the concept of 'imagetext': counteraction as providing a methodological strategy for knowledge production beyond the confines of the containing medium; and the mediality of illustration as a three-part relation between the image–text–media of reproduction rather than the two-part relation of the image–text.